Rectal carcinosarcoma: A case report and review of literature - Tsekouras, Dimitrios Konstantinos (Baishideng Publishing Group Co., Limited, 2006)
A 60-years old male was admitted to our department for investigation of constipation and hypogastric discomfort intensified during defecation of a few weeks duration. The cause proved to be a rectal carcinosarcoma that was treated by abdominoperineal resection and postoperative chemo-radiotherapy. The patient died 6 months later due to hepatic failure, showing evidence of disseminated disease. In general colonic carcinosarcomas constitute a rare category of malignant neoplasms whose nature is still incompletely understood. No specific treatment guidelines exist. Surgery is the mainstay of treatment and regardless of the addition of adjuvant therapy the prognosis is very poor. Systematic genetic analysis may be the clue for understanding the pathogenesis of these mysterious tumors.